Analisis Hadist Tentang Memuliakan Guru dan Relevansinya dengan Dunia Modern - Erlin Ramadhani; Shobrun Jamil; Fahni Adniaty; Gendis Zulfa Ziana; Ahmad Hasby Baihaqi Nasir (STIQ Miftahul Huda Rawalo, 2025)
In Islamic teachings, teachers occupy a very special position as bearers of knowledge, guides of morals, and leaders of the people towards the path of righteousness. This virtue is emphasized through a number of hadiths of the Prophet Muhammad ﷺ which reveal the nobility of those who teach knowledge. The hadiths studied include explanations of the prayers of angels and creatures of Allah for teachers of goodness, scholars as heirs to the prophets, and useful knowledge as a charitable deed whose rewards are unending. This article aims to review in depth the contents of these hadiths while highlighting their relevance in today's education. This study uses a literature review approach by examining primary and secondary sources related to the theme of teachers and Islamic education. The results of the study confirm that teachers not only play a role as teachers of subject matter, but also as role models who shape the character, morals, and spirituality of students. The great reward promised to those who teach knowledge is an encouragement for educators to work sincerely and professionally. By understanding the position of teachers according to the hadith, it is hoped that a collective awareness will grow to respect, support, and emulate their role in building a noble civilization.